2022
DOI: 10.1186/s13046-022-02519-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific modeling of stroma-mediated chemoresistance of pancreatic cancer using a three-dimensional organoid-fibroblast co-culture system

Abstract: Background Cancer-associated fibroblasts (CAFs) are considered to play a fundamental role in pancreatic ductal adenocarcinoma (PDAC) progression and chemoresistance. Patient-derived organoids have demonstrated great potential as tumor avatars for drug response prediction in PDAC, yet they disregard the influence of stromal components on chemosensitivity. Methods We established direct three-dimensional (3D) co-cultures of primary PDAC organoids and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 59 publications
5
31
0
Order By: Relevance
“…indicated that knockdown L1CM human colorectal tumoroids presented improved sensitivity to irinotecan. The coculture system of pancreatic ductal adenocarcinoma (PDAC) organoids and CAFs showed resistance to gemcitabine, 5‐FU, and paclitaxel, with increased epithelial‐to‐mesenchymal transition (EMT) gene expression in these organoid cells 231 . Colorectal tumoroids were used to perform drug sensitivity assays and pharmacogenomics analysis, and results showed that the paclitaxel sensitivity was linked to the checkpoint with forkhead and ring finger domains (CHFR) silencing in organoid as well as in xenograft models 232 .…”
Section: Biomedical Applications Of Organoidsmentioning
confidence: 99%
“…indicated that knockdown L1CM human colorectal tumoroids presented improved sensitivity to irinotecan. The coculture system of pancreatic ductal adenocarcinoma (PDAC) organoids and CAFs showed resistance to gemcitabine, 5‐FU, and paclitaxel, with increased epithelial‐to‐mesenchymal transition (EMT) gene expression in these organoid cells 231 . Colorectal tumoroids were used to perform drug sensitivity assays and pharmacogenomics analysis, and results showed that the paclitaxel sensitivity was linked to the checkpoint with forkhead and ring finger domains (CHFR) silencing in organoid as well as in xenograft models 232 .…”
Section: Biomedical Applications Of Organoidsmentioning
confidence: 99%
“…(Figure 4b) CAFs, as important components of the tumor microenvironment, have been extensively shown to support the development and progression of cancer and to promote therapeutic resistance. [5,8,13] The clinical importance of CAFs in disease progression, treatment response, and patient prognosis has been widely reported in diverse types of cancer. [7] CAFs secrete various chemokines, cytokines, and growth factors to produce a tumorpermissive microenvironment.…”
Section: Preservation Of Fibroblast Stroma Within Patient-derived Tum...mentioning
confidence: 99%
“…It promotes tumor development, invasion, and metastasis. [8] CAFs also have the capacity to shape the www.advmattechnol.de extra-tumor stroma, forming a barrier to drug or therapeutic immune cell penetration by blocking deeper penetration of drugs and immune cells into tumor tissue, thereby reducing the effectiveness of tumor therapy. [7,9] Histopathological analysis has shown that the abundance of CAFs correlates with the prognosis of different human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Many publications showed that organoid models could accurately recapitulate this biological heterogeneity and maintain phenotypic and genetic characteristics of original tumor epithelium. Moreover, tumor organoid cultures seem to be suitable for modeling the TME heterogeneity and cell interactions using co-culture with different type of cells, such as cancer-associated fibroblasts (CAFs) 37,38 or immune cells. 39,40 As mentioned above, hypoxia, which greatly contributes to malignant behavior and chemo- and radio-resistance, does develop in organoids once they reach a certain size.…”
Section: Tumor Organoidsmentioning
confidence: 99%